Analisa Efisiensi Biaya promosi Dalam Meningkatkan Volume Penjualan Pada PT . PDAM Tirta Pakuan Bogor - Apriliandini, Venny; M, Annaria Magdalena (Jurnal Ilmiah Akuntansi Kesatuan, 2016)
Promotion is an activity conducted by the company with the aim to inform, persuade, and affect consumers in choosing or buying a product offered by the company. With cost efficiency promotion budgeted by several companies proved in significant sales volume reduced or in other words, sales volumes remained stable. Thus, the expected income will be optimal. Therefore, it is important to support the cost of promotional sales, and at the same time keep the efficiency of budgetary expenditures or budget these costs to keep sales and income increased. The purpose of this study was to analyze the cost efficiency of the campaign carried out by the PDAM to improve or stabilize sales volume. So that management can have a view of realization and evaluation costs promotion sales volume. The research results showed that PDAM Tirta Pakuan are to improve efficiency in its promotional activities. This is indicated in the year 2013, PDAM realization promotional costs lower than its promotional budget. But volume sales in 2013 PDAM did not experience a significant decrease in sales volume, thus can be said sales volume in 2013 remained stable as in previous years. Evaluation results from these studies show that the efficiency of the cost of promotion does not significantly affect the sales volume into decreasing. By applying the cost efficiency of volume sales promotion, we can conclude that PDAM remain stable, and PDAM is spending lower costs for promotional activities. Therefor, profits or advantages from the company will increase compared to the previous year.